Analsis Karakteristik Fisik dan Kimia Surimi Ikan Lele dengan Perlakuan Jenis dan Lama Penyimpanan Dingin - Dasir Dasir; Suyatno Suyatno; Rosmiah Rosmiah (Seminar Nasional Lahan Suboptimal, 2018)
Dasir et al, 2019. Analysis of Physical and Chemical Characteristics of Surimi Lele Fish with Treatment Treatment and Cold Storage Duration. pp. 165-171.Currently, fish farmers have successfully cultivated catfish, catfish, and tilapia with increasing production every year. The types of fish have not been used in the manufacture of Pempek because of poor meat quality. Therefore, it is necessary to improve quality by making it a product between of surimi. This study aimed to determine the chemical characteristics and physics of catfish surimi from the treatment of cold storage and cold storage. The research design used was factorial completely randomized design (RALF) with cold storage type and time using ice, (P1) and with freezer (P2) for 0, 3, 6 and 9 days (W1, W2, W3,  and W4) with two Repeat times. In the interaction treatment, the highest protein content was 11.93% in P1W0, the lowest water content was 71.33% in P2W0, the highest pH was 7.36 in P1W3 and the lowest EMC was 21.58% in P1W0. The highest organoleptic test results on color and aroma 3.50 on P1W0 and physical test on the highest texture value of 6.45 on P1W3. The results of the study concluded that the P1W3 treatment showed the best results.